Role of Resolvins in the Inflammatory Resolution of Neurological Diseases - Li, Chunrong; Wu, Xiujuan; Liu, Shan; Shen, Donghui; Zhu, Jie; Liu, Kangding (Frontiers in Pharmacology, 2020)
Abstract The occurrence of neurological diseases including neurodegenerative disorders, neuroimmune diseases, and cerebrovascular disorders is closely related to neuroinflammation. Inflammation is a response against infection or injury. Genetic abnormalities, the aging process, or environmental factors can lead to dysregulation of the inflammatory response. Our immune system can cause massive damage when the inflammatory response becomes dysregulated. Inflammatory resolution is an effective process that terminates the inflammatory response to maintain health. Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) are omega-three polyunsaturated fatty acids that play a crucial regulatory role in the development of inflammation. Resolvins (Rvs) derived from EPA and DHA constitute the Rvs E and Rvs D series, respectively. Numerous studies on the effect of Rvs over inflammation using animal models reveal that they have both anti-inflammatory and pro-resolving capabilities. Here, we review the current knowledge on the classification, biosynthesis, receptors, mechanisms of action, and role of Rvs in neurological diseases.